Estudos por QSAR, docagem e dinâmica molecular de derivados de quinazolina tendo como alvo a proteína beta tubulina para o controle da fusariose - Gasques, Larissa de Souza (2024)
Gibberellosis or ear fusariosis is a disease caused by phytopathogenic fungi such as Fusarium graminearum. Significant losses in agriculture and impacts on the global economy are evidenced by the disease, which is minimized by the use of commercial fungicides. In this scenario, it is important to create new fungicides that are more efficient and, preferably, less harmful to the environment. This work describes computational studies applied to a set of quinazoline-derived molecules that were synthesized and previously evaluated for their fungicidal activity against F. graminearum in the literature. The selected compounds served as prototypes for the construction of the 2D and 3D QSAR models (CoMFA and CoMSIA), where satisfactory results were obtained during validation. Topological descriptors (JGI1 and VE3_D) were able to predict the QSAR-2D model with q² = 0.743, r² = 0.797 and r²test = 0.764. In CoMFA, q² = 0.834, r² = 0.958, and r²test = 0.834 were obtained with the set of molecules loaded by the RESP HF 6-311G method. The best model in CoMSIA, on the other hand, was derived from atomic partial charges using the Gasteiger-Marsili empirical method, obtaining a q² = 0.956, r² = 0.987 and r²test = 0.858 using the electrostatic and hydrophobic descriptors. The QSAR models were used to predict the biological activity of triazole compounds from the library belonging to our research group. The derivatives that stood out at this stage were sent for molecular docking analysis, which revealed the intermolecular interactions at the compounds' binding sites and compared them with the fungicide carbendazim. This study revealed that compound T15 was favorable to toxicity tests by ProTox II, as well as by the QEPest program. Then, a 200 ns molecular dynamics simulation was carried out to evaluate the behavior and stability of compound T15 and to compare it with carbendazim. The analyses suggest that the triazole (a thymol derivative) was stable during the simulation, performing more intermolecular interactions at the β-tubulin active site than the commercial fungicide. MM/GBSA results predict that its binding free energy was -44 kcal/mol, while carbendazim -18 kcal/mol. The results reveal that T15 proved to have an ability to inhibit fusarium, since its interaction with the protein is stronger. Therefore, it can be concluded that the models built in this work were able to predict and identify a promising compound with optimal predicted biological activity